2015
DOI: 10.1080/19443994.2014.907749
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae removal from Ghrib Dam (Ain Defla, Algeria) water by electroflotation using stainless steel electrodes

Abstract: A B S T R A C TThis study investigates the microalgae removal from Ghrib Dam water by electroflotation (EF) using stainless steel electrodes. The results obtained show that EF is excellent in microalgae removal (~100%). The effects of parameters such as: current density (i), initial pH and distance between electrodes (d) are examined. The optimal conditions are: i = 170 A m −2 and d = 1 cm during 15 min at pH 7.8. Future research must focus on microalgae lysis, toxin release and degradation due to EF treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…De Carvalho Neto et al [214] reported a chlorophyll a removal efficiency of 99% using an electroflotation method running for 140 min with a power supply of 60 W. Ghernaout et al [215] reported a microalgae removal efficiency of approximately 100% after 140 minutes in Ghrib Dam water using electroflotation method. Shelef et al [43] noted that electroflotation technique resulted in total suspended solids in the range of 3-5%.…”
Section: Reusability Of Mediamentioning
confidence: 99%
“…De Carvalho Neto et al [214] reported a chlorophyll a removal efficiency of 99% using an electroflotation method running for 140 min with a power supply of 60 W. Ghernaout et al [215] reported a microalgae removal efficiency of approximately 100% after 140 minutes in Ghrib Dam water using electroflotation method. Shelef et al [43] noted that electroflotation technique resulted in total suspended solids in the range of 3-5%.…”
Section: Reusability Of Mediamentioning
confidence: 99%
“…Recently, Ghernaout et al investigated the microalgae collection from Ghrib Dam water in Algeria using electroflotation with stainless steel electrodes and the microalgae harvesting efficiency of about 100% was reached, suggesting that electroflotation would be an excellent microalgae harvesting technology. Also de Carvalho Neto et al successfully applied electroflotation for microalgae harvesting and cell disruption.…”
Section: Methods To Induce Flotationmentioning
confidence: 99%
“…As mentioned previously, EC stays a viable solution for classical coagulation, During EC process, there are two induced phenomena: electrophoresis and electroflotation [75]; separately, they are well known in electrochemistry's applications and well developed technically and mathematically [76]. How important are these inherent phenomena in EC process efficiency, particularly in removing pathogens deserves more focus [77].…”
Section: Ec Next Tendenciesmentioning
confidence: 99%